2002
DOI: 10.1071/sr02031
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium accumulation by willow clones used for soil conservation, stock fodder, and phytoremediation

Abstract: Elevated levels of cadmium are often found in the soil of New Zealand pasturelands due to the long-term use of Cd-contaminated fertilisers. The accumulation of Cd in willow biomass used as stock fodder could therefore adversely affect agricultural productivity and human health. Alternatively, willows may be used for phytoremediation of Cd-contaminated soil at polluted sites. An investigation was carried out to determine the variation in Cd as well as Zn, Mn, and Fe accumulation in 15 willow clones that had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…4). Willows on uncontaminated and slightly contaminated soils typically have high foliar BCF for Cd and Zn (Granel et al, 2002;Meers et al, 2003;Rosselli et al, 2003), while lower BCF for Cd and Zn on polluted DSDS were found for several willow species (Vandecasteele et al, 2004). These findings indicate that the use and value of willows for phytoextraction might be restricted to soils where Cd and Zn concentrations are only slightly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…4). Willows on uncontaminated and slightly contaminated soils typically have high foliar BCF for Cd and Zn (Granel et al, 2002;Meers et al, 2003;Rosselli et al, 2003), while lower BCF for Cd and Zn on polluted DSDS were found for several willow species (Vandecasteele et al, 2004). These findings indicate that the use and value of willows for phytoextraction might be restricted to soils where Cd and Zn concentrations are only slightly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Many willow species are very vigorous growers and are characterized by particular physiological adaptation (Park et al 2008). The economic importance of the various species is currently increasing and emerging in a wide array of practical application to restore damaged ecosystems including phytoremediation and bioengineering such as the production of biofuels (Perttu and Kowalik 1997;Granel et al 2002;Vervaeke et al 2003;Kuzovkina and Quigley 2005). Salix tetrasperma Roxb.…”
Section: Introductionmentioning
confidence: 99%
“…Salicaceae are also reported to grow even in severe soil conditions and to accumulate heavy metals , Berndes et al 2004). Many studies have thus been focused on the use of willows and pop lars in phytoextraction (Riddell-Black 1994, Labreque et al 1995, Bañuelos et al 1999, Robinson et al 2000, Aronsson & Perttu 2001, Granel et al 2002, Klang-Westin & Perrtu 2002, Hammer et al 2003, Vyslouz ilová et al 2003, Vervaeke et al 2003, Madejou et al 2004, Sebastiani et al 2004, Kuzovkina et al 2004, Robinson et al 2005, Giachetti & Sebastiani 2006, Dos Santos Ut mazian et al 2007, Jensen et al 2009). These species can be ad vantageously exploited in short rotation cop pice cultures (SRC), a strategy whose appli cation in phytoremediation presents intere sting and economically promising perspe ctives (Scarascia-Mugnozza et al 1997, Paulson et al 2003, Laureysens et al 2004a, Laureysens et al 2004b, Rockwood et al 2004, Dickinson & Pulford 2005, Witters et al 2009).…”
Section: Woody Plants and Phytoremediationmentioning
confidence: 99%